The making of IT teachers: lessons learned from animation-enhanced training - Hanafi Hafizul F., Samsuddin Khairulanuar, M. Nordin Norhisham, Abas Ashardi, Said Che Soh, (N/A, 2012)
The making of IT teachers: lessons learned from animation-enhanced training by Hanafi Hafizul F., Samsuddin Khairulanuar, M. Nordin Norhisham, Abas Ashardi, Said Che Soh,